Effects of Prevocational Education on the Vocational Knowledge and Attitudes of Students-Teachers in Jordan - Al-Tweissi, Ahmad Issa (Journal of Education and Vocational Research, 2012)
This study aimed at investigating the effect of studying Pre-Vocational Education (PVE) on the class-teacher/students in Jordanian universities. The sample of the study consisted of (57) studentsteachers. A self-completed questionnaire and knowledge test were developed and then employed for the purpose of the research. Their validity and reliability were by all odds verified. The research main findings revealed the followings; (a) students-teachers’ vocational knowledge has been significantly improved, their achievement marks rose from (40.38)to (72.45); (b) students-teachers’ attitude has been favourably improved with an overall mean score rose from (3.19) to (3.31); (c) while it is reported that there was a statistical significant difference in students-teachers’ achievement in vocational knowledge, and in favour of female there was no statistical significant difference in their attitudes due to the gender variable. Based upon the research main findings, several recommendations, germane to the development of PVE course were proposed.